2022
DOI: 10.3389/fphar.2022.1052113
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine exposure levels to optimize treatment outcomes in opioid use disorder

Abstract: The severity of the ongoing opioid crisis, recently exacerbated by the COVID-19 pandemic, emphasizes the importance for individuals suffering from opioid use disorder (OUD) to have access to and receive efficacious, evidence-based treatments. Optimal treatment of OUD should aim at blocking the effects of illicit opioids while controlling opioid craving and withdrawal to facilitate abstinence from opioid use and promote recovery. The present work analyses the relationship between buprenorphine plasma exposure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Buprenorphine plasma concentrations were modeled in relation to several key clinical endpoints (suppression of withdrawal and craving, and blockade of opioid liking and drug-seeking behavior). This analysis confirmed that concentrations in the 2–3 ng/mL range are effective in producing broad clinical benefits on these measures ( Laffont et al., 2022 ). This comprehensive analysis further identified several individual differences in these PK/PD relationships, including demographic, genetic, and social factors, which are an important topic of future study for optimizing outcomes.…”
Section: The Regulatory Approval Of Buprenorphine For the Treatment O...supporting
confidence: 61%
“…Buprenorphine plasma concentrations were modeled in relation to several key clinical endpoints (suppression of withdrawal and craving, and blockade of opioid liking and drug-seeking behavior). This analysis confirmed that concentrations in the 2–3 ng/mL range are effective in producing broad clinical benefits on these measures ( Laffont et al., 2022 ). This comprehensive analysis further identified several individual differences in these PK/PD relationships, including demographic, genetic, and social factors, which are an important topic of future study for optimizing outcomes.…”
Section: The Regulatory Approval Of Buprenorphine For the Treatment O...supporting
confidence: 61%
“…From a pharmacological standpoint, an adequate maintenance dose of buprenorphine will 17,18 1. Eliminate negative reinforcement by suppressing opioid withdrawal symptoms and craving that can lead to illicit opioid use, 2.…”
Section: Treatment Goals and Dose Adequacymentioning
confidence: 99%
“…People who inject opioids may especially benefit from higher buprenorphine doses, according to findings from a 2022 trial of monthly extended-release buprenorphine (XR-BUP) subcutaneous injections 18 . Participants with a history of injection use were more likely to remain opioid-abstinent at the higher dose (300 mg monthly for 6 months) compared with the lower dose (300 mg monthly for 2 months, then 100 mg monthly for 4 months), whereas participants with no injection history experienced abstinence at the same rate on both regimens.…”
Section: Dosing Evidence From Clinical Researchmentioning
confidence: 99%
“…The 100-mg maintenance dose was selected to maintain buprenorphine plasma concentrations of 2–3 ng/mL achieved with the two initial monthly doses of 300 mg [ 27 ]. Alternatively, the 300-mg maintenance dose provides higher plasma concentrations of buprenorphine at steady state (5–6 ng/mL), which some patients may need given their drug use history and clinical condition [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid blockade, craving, withdrawal, and abstinence data from BUP-XR Phase 2 and Phase 3 studies in patients with moderate-to-severe OUD showed that buprenorphine plasma concentrations sustained at 2–3 ng/mL (corresponding to ≥ 70% brain mu -opioid receptor occupancy) optimized treatment outcomes in most patients, whereas some individuals needed higher concentrations [ 28 ]. Specifically, exposure–response modeling of opioid abstinence data pointed toward differences in the opioid-injecting subpopulation, suggesting that this population would benefit from higher buprenorphine plasma concentrations delivered by the 300-mg maintenance dose of BUP-XR [ 28 ]. This finding is consistent with studies from the literature indicating that participants who use the highest dose opioid, including those who inject, likely require higher doses of mu -opioid receptor full agonist (e.g., methadone) or partial agonist (e.g., buprenorphine) to achieve efficacy [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%